Early and guided physiotherapy in head and neck cancer: a narrative review of clinical interventions - Nainwal, Deepak; Sandilya, Abhishek Kumar (International Journal of Research in Medical Sciences, 2025)
Head and neck cancer (HNC) patients frequently experience pain, fatigue, dysphagia, and psychological distress because of oncologic treatment. Physiotherapy has emerged as a key rehabilitative strategy to address these sequelae, particularly when initiated early and delivered through therapist-guided protocols. Objective: This narrative review aims to synthesize evidence from clinical trials and structured programs evaluating early and guided physiotherapy interventions in HNC, focusing on their impact on symptom management and functional recovery. A comprehensive literature search was conducted across five databases (PubMed, Scopus, Web of Science, Cochrane Library, and ScienceDirect) for studies published between 2010 and 2025. A total of 396 records were identified, with 304 screened by title and abstract. After full-text assessment of 141 articles, 13 studies met the inclusion criteria. Data were extracted on intervention type, timing, therapist involvement, and outcomes related to pain, fatigue, swallowing function, and quality of life. Early physiotherapy interventions, particularly those involving therapist supervision, demonstrated consistent improvements in fatigue, mobility, swallowing function, and emotional well-being. Multimodal approaches combining aerobic and resistance training were especially effective. Therapist-guided delivery enhanced adherence, safety, and individualized care. Early and guided physiotherapy offers significant benefits for HNC patients, supporting its integration into multidisciplinary cancer rehabilitation. Future research should focus on standardized protocols, long-term outcomes, and scalable delivery models.